ChemInform Abstract: Diels—Alder Reaction of Tropones with Arynes: Synthesis of Functionalized Benzobicyclo[3.2.2]nonatrienones. Issue 42 (14th October 2014) - Thangaraj, Manikandan; Bhojgude, Sachin Suresh; Bisht, Rajesh H.; Gonnade, Rajesh G.; Biju, Akkattu T.
Abstract A new procedure for the mild, practical, and scalable Diels—Alder reaction of tropones with arynes is reported.